Optimization of plasma amplifiers - Sadler, J; Trines, R; Tabak, M; Haberberger, D; Froula, D; Davies, A; Bucht, S; Silva, L; Alves, E; Fiuza, F; Ceurvorst, L; Ratan, N; et al. (American Physical Society, 2017)
Plasma amplifiers offer a route to side-step limitations on chirped pulse amplification and generate laser pulses at the power frontier. They compress long pulses by transferring energy to a shorter pulse via the Raman or Brillouin instabilities.We present an extensive kinetic numerical study of the three-dimensional parameter space for the Raman case. Further particle-in-cell simulations find the optimal seed pulse parameters for experimentally relevant constraints. The high-efficiency self-similar behavior is observed only for seeds shorter than the linear Raman growth time. A test case similar to an upcoming experiment at the Laboratory for Laser Energetics is found to maintain good transverse coherence and high-energy efficiency. Effective compression of a 10 kJ, nanosecond-long driver pulse is also demonstrated in a 15-cm-long amplifier.